Convergence of Criminal Law Instruments in the Misuse of Firearms by Police Officers: A Review of the Criminal Code, the Police Law, and the Human Rights Law - Ari Eko Prasetyawan, Ari Eko Prasetyawan; Edi Saputra Hasibuan, Edi Saputra Hasibuan; Diana Fitriana, Diana Fitriana (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2025)
The misuse of firearms by members of the Indonesian National Police is a complex legal issue that has a direct impact on the guarantee of human rights, especially the right to life. This article aims to examine the convergence of criminal law instruments governing the use of firearms by members of the Indonesian National Police, as well as evaluating the criminal and disciplinary liability system in the context of such abuse of authority. This research uses a normative juridical method with a legislative approach and case studies. The results of the study show that although normative arrangements related to the use of firearms are available through the Criminal Code, Law No. 2 of 2002, and a number of Perkapolri, the implementation is still weak, especially in the aspects of supervision and accountability. There is a discrepancy between norms and practices, as well as a tendency for non-transparent internal settlements. This condition shows that substantive legal convergence has not been realized. Therefore, it is necessary to reformulate the accountability system that includes harmonizing regulations, strengthening independent oversight institutions, and integrating human rights principles in the entire law enforcement process. Thus, the Indonesian legal system can guarantee justice and prevent impunity among law enforcement officials.